Pengaruh Studi Karakteristik Getaran Shock Breaker Pada Sepeda Motor Matic 110 CC - Achmad Noerdien; Gatut Rubiono; ikhwanul Qiram (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2018)
A matic motorcycle 110 cc is one of kinds of motorcycle that many used by the modern people, especially for the narrow streets with high level mobility. One of aspects to beconsidered in this vehicle design is a level of comfort and safety in reducing the vehicle due to environmental conditions. The purpose of the research is to get the characteristics of shock breakerin matic motorcycle 110 cc with three motorcycle brands due to road profiles. The research was conducted with road profile model (flatten, slightly wavy and wavy) at Rpm speed (1700, 3500, 4000 and 5000). Vibration was calculated based on the speed of circle engine (Rpm) using vibration’s meter. Measurements were done at 3 points in the shock beaker, rider and passenger with 60 seconds 20 seconds. The results showed that the greater the engine speed (Rpm), the vibration tends to be smaller, whereas the smaller the engine speed (Rpm), the vibrations tend to large.